2023
DOI: 10.3390/ijms24065983
|View full text |Cite
|
Sign up to set email alerts
|

A Role of Sodium-Glucose Co-Transporter 2 in Cardiorenal Anemia Iron Deficiency Syndrome

Abstract: Heart failure, renal dysfunction, anemia, and iron deficiency affect each other and form a vicious cycle, a condition referred to as cardiorenal anemia iron deficiency syndrome. The presence of diabetes further accelerates this vicious cycle. Surprisingly, simply inhibiting sodium-glucose co-transporter 2 (SGLT2), which is expressed almost exclusively in the proximal tubular epithelial cells of the kidney, not only increases glucose excretion into the urine and effectively controls blood glucose levels in diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 77 publications
0
4
0
1
Order By: Relevance
“… 46–48 Cluster #7 focused on the involvement of Sodium-Glucose Co-Transporter 2 (SGLT2) in HF during energy metabolism regulation, hemodynamics, erythropoiesis, iron bioavailability and inflammatory set points. 49 The clinical findings are inspiring, and empagliflozin, by simply inhibiting SGLT2 expressed in renal tubular epithelial cells, not only effectively controls blood glucose levels, but also improves the prognosis of HF. 50 , 51 SGLT2 inhibitor, one of the hotspots in the field of HF, has recently been proven to increase hemoglobin levels, 52 which reinforces its position in the treatment of anemia in HF.…”
Section: Discussionmentioning
confidence: 99%
“… 46–48 Cluster #7 focused on the involvement of Sodium-Glucose Co-Transporter 2 (SGLT2) in HF during energy metabolism regulation, hemodynamics, erythropoiesis, iron bioavailability and inflammatory set points. 49 The clinical findings are inspiring, and empagliflozin, by simply inhibiting SGLT2 expressed in renal tubular epithelial cells, not only effectively controls blood glucose levels, but also improves the prognosis of HF. 50 , 51 SGLT2 inhibitor, one of the hotspots in the field of HF, has recently been proven to increase hemoglobin levels, 52 which reinforces its position in the treatment of anemia in HF.…”
Section: Discussionmentioning
confidence: 99%
“…Research indicated that the incidence and prevalence of diabetic patients were often related to erythropoietin deficiency caused by diabetic kidney damage [51]. The interaction of heart failure, renal dysfunction, anemia, and iron deficiency form a vicious cycle and diabetes further accelerates this vicious cycle [52]. Therefore, diabetic patients might be more likely to suffer from low hemoglobin symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of iron deficiency/anemia in the development of all the diseases presented in the graphical abstract is at best noticed, although it might further help to clarify more fundamental mechanisms involved in disease progression. Recognizing a significant drop in hemoglobin as a sign of local glucose deprivation should start a clinical search for the underlying causes in order to prevent a vicious cycle where different diseases, such as insulin resistance and iron deficiency, affect each other (graphical abstract; [ 229 ]). Nutrition or the precautionary intake of phytochemicals with their anti-inflammatory effect might also help to improve cellular glucose import ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%